Analisis Biaya Satuan dan Kualitas Hidup Penderita Gagal Ginjal Kronik yang Menggunakan Tindakan Hemodialisis di Rumah Sakit Tebet Tahun 2015 - Nabila, Anggun (UI Scholars Hub, 2015)
The research aims to describe unit cost of hemodialysis and quality of life of Chronic Kidney Disease patients who use hemodialysis as a therapy at Tebet Hospital in 2015. Unit cost is calculated based on hospital perspective. Developing questioner of quality of life of Chronic Kidney Disease (CKD) patients (Dialysis Health Related Quality of Life) and clinical pathway of hemodialysis. Dialysis Health Related Quality of Life has 13 dimensions (sense of taste, sleep disorders, mobility, fatigue, anxiety, emotional, pain, self-care, daily activities (working, shopping, study, travelling, etc), communication, social interaction, being isolated, the burdens of others), measuring utility and time preference of patients who use hemodialysis as a therapy. QALY’s score is 3,35 which means patient of CKD gets 3 years of quality life. While using hemodialysis, utility score is 0,6, 0 means death and 1 means healthy life, and time preference score is 5,1 years, which means patient of CKD gets 5 more years when they use hemodialysis as a therapy. Unit cost of single use of hemodialysis is Rp 1.315.644,- Unit cost of hemodialysis for 6 months with 2 times a week of hemodialysis is Rp 41.324.355,-. Costs include screening of dialysis indication, single use dialysis, regular medical check up, and virus marker. The implication of clinical pathway is needed for quality and cost control.